Variations in Milk Yield and Composition Between Fore and Rear Udder-Halves in She-Camel (Camelus Dromedarius) - Eisa, M.O.; Hassabo, A.A. (Pakistan Journal of Nutrition, 2009)
Total number of Sixteen she-camels were chosen from a large herd of camel belonging to the Lahween tribe in Eastern Sudan. The breed is known locally as Arabi-Lahwee. The fore and rear udder-halves measurements including, depth and height of the udder, distances, diameter and length of the teats. The results revealed that the depth of fore quarters was 20.9+0.75 cm and which was significantly (p